TEACHING FOREIGN LANGUAGES WITH THE HELP OF TECHNOLOGY: OPPORTUNITIES AND CHALLENGES - Assoc. Prof. Dildora M. Yuldasheva (Bright Mind Publishing, 2025)
Information and communication technology (ICT) have become essential to contemporary education, markedly improving the efficacy of foreign language instruction. This article examines the educational ideas, modern technologies, and techniques that support technology-enhanced foreign language teaching. This document examines current improvements in Uzbekistan's foreign language education system, emphasizing the incorporation of ICT and highlighting the associated opportunities and concerns. The study highlights the beneficial effects of ICT utilization, including enhanced student involvement, improved communication abilities, and the encouragement of independent learning, based on national and international research. Notwithstanding these advantages, numerous challenges impede comprehensive implementation, including inadequate digital skills among instructors, insufficient technical infrastructure, and a scarcity of regional methodological resources. The article promotes focused professional development, infrastructural improvement, and the development of novel educational resources to tackle these issues. The incorporation of digital technologies in foreign language instruction is essential for enhancing educational quality and aligning with international educational standards. This study provides significant insights for policymakers, educators, and academics seeking to enhance the application of ICT in language teaching in Uzbekistan and analogous settings.
Keywords: Technology-Enhanced Learning Digital Education Online Learning Platforms Multimedia Resources Autonomous Learning Student Engagement Educational Innovations Uzbekistan Education System.